2022
DOI: 10.3389/fimmu.2022.960444
|View full text |Cite
|
Sign up to set email alerts
|

The divergence between T cell and innate lymphoid cell fates controlled by E and Id proteins

Abstract: T cells develop in the thymus from lymphoid primed multipotent progenitors or common lymphoid progenitors into αβ and γδ subsets. The basic helix-loop-helix transcription factors, E proteins, play pivotal roles at multiple stages from T cell commitment to maturation. Inhibitors of E proteins, Id2 and Id3, also regulate T cell development while promoting ILC differentiation. Recent findings suggest that the thymus can also produce innate lymphoid cells (ILCs). In this review, we present current findings that su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 178 publications
0
2
0
Order By: Relevance
“…T cells develop from multipotent progenitors (MPPs) or common lymphoid precursors (CLPs) in the thymus (Pankow & Sun, 2022). T cell differentiation produces subcells namely CD4 + helper cells (Th1 and Th2), cytotoxic CD8+ (CTL/Tc/Ts/Tr/Th3), and memory T cells (Baratawidjaja & Rengganis, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…T cells develop from multipotent progenitors (MPPs) or common lymphoid precursors (CLPs) in the thymus (Pankow & Sun, 2022). T cell differentiation produces subcells namely CD4 + helper cells (Th1 and Th2), cytotoxic CD8+ (CTL/Tc/Ts/Tr/Th3), and memory T cells (Baratawidjaja & Rengganis, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies suggest that E proteins play a vital role in the development of memory CD8+ T cells, and is crucial for long-term immunity against viral infections [18,19]. Conversely, other researchers have shown that Id proteins suppress T cell activation and proliferation, and the loss of Id2 or Id3 can trigger T cell responses and autoimmunity [20][21][22][23]. The latest studies have also discovered new roles of E and Id proteins in the differentiation and functioning of regulatory T cells, critical for maintaining immune tolerance and preventing autoimmune diseases [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%